Trastornos de la conducta alimentaria y relación con la disfunción familiar en las estudiantes de la Unidad Educativa la Inmaculada de Loja. - Arévalo Calderón, Karla Vanessa (2016)
Eating disorders are diseases that can cause serious disturbances in the daily diet, such as eating very small amounts or overeating. Several studies have determined that the significant annual increase in these disorders depends on many factors; one of the most important is family dysfunction. The aim of this study was to establish the relationship between eating disorders and family dysfunction; the study applied an eating attitudes test and FF-SIL questionnaire that assesses family functioning. It was established that 84% of student participants had eating disorders and more than a third of families had family dysfunction, mainly moderate dysfunction. When establishing the relationship between eating disorders and family dysfunction, a strong statistical association was noticed which was demonstrated using an OR of 9.25, and a confidence interval of 3-47-24.62, this was also reflected in the value of P 0.000002 that was lower than the set value of 0.05 which determined a statistical significance. A descriptive cross-sectional study was designed and conducted at "La Inmaculada” Fiscomisional Educational Unit which included a total of 600 female students aged between 12 and 17 years old. The study also had a standard deviation of ± 2.5 and a confidence interval of 95%. A 235 student sample was obtained by applying a specific formula, but for legal reasons, lack of parental consent and expressed refusal to participate in this study, the actual study sample consisted of only 118 students, which were chosen randomly, according to the number required. The analysis and data tabulation were done using the SPSS program which allowed the development of tables and graphs. By means of a 2x2 analysis table, Epi Info software enabled us to obtain the variables of probability ODD ratio and P value for statistical significance. Keywords Disorder eating behavior - Family dysfunction-adolescents.